Acessibilidade do turismo no espaço rural: um estudo da rota Agrobiratã - Rosa, Daniel Garcia da (2024)
This dissertation addresses accessibility in rural tourism, focusing on the Agrobiratã Route, investigating the adequacy of rural tourism enterprises along the Agrobiratã Route for people with disabilities. The main objective was to analyze the accessibility conditions at the tourist sites along the route, checking compliance with legal standards and the needs of tourists with disabilities. The study also aimed to identify the challenges and opportunities for promoting more inclusive tourism in the region. The research adopted a qualitative approach, using data collection methods through direct observation, with on-site visits to properties and informal conversations with the owners. A checklist was used, allowing for a systematic evaluation of observable accessibility aspects in the studied areas. Data sources include the owners of the enterprises along the Agrobiratã Route. Data collection was done through direct observation, and data analysis was conducted using the SWOT tool. The results indicated that, although the Agrobiratã Route has initiatives toward accessibility, many enterprises still present physical and attitudinal barriers that limit the full inclusion of people with disabilities. Furthermore, the lack of adequate infrastructure and the scarcity of specific training for tourism workers are significant challenges. Key conclusions highlight the need for greater awareness of accessibility, investment in infrastructure, and continuous training for sector workers to ensure truly inclusive tourism in rural areas.